Implementasi Pembentukan Organisasi Pelajar (IPNU/IPPNU) Dalam Mengembangkan Potensi Siswa Di Madrasah - Ratih Kusuma Ningtias (PARTISIPATORY, 2022)
This companion focuses on the formation of student organizations at MTs Al-Fattah Sugihan. With the existence of this student organization, it is a place to develop the potential of these students which is very limited. In accordance with the instructions of the Great Leadership of the Ma'arif NU Educational Institute to establish a student organization in order to be able to develop student potential, which previously did not exist in this institution. One of the instruments used to provide solutions to problems or problems developing in institutions is through research based on Participatory Action Research (PAR). one of the research models that seek to link the research process into the process of social change. The social change in question is how the empowerment process can create three benchmarks, namely the existence for a joint commitment with the community, the existence a local leader in the community and the existence of a new institution in the community that is built based on needs. From the Introduction and Establishment of Organizations that we have done together with the teachers and students, we have built a Student Organization which is expected to become a forum for developing student potential. With the formation of the management of the IPNU-IPPNU Organization, it can be a real example that in an institution there is a need for a student organization, which can be a place for students to learn and manage a group to provide them with later life in society.